A Linguistic Analysis of the Social Dialect(S) Spoken by the Slum Dwellers in Lahore - Nabeel, Jannat; Kashif, Farah; Khurshid, Maryam (Annals of Human and Social Sciences, 2024)
The study aimed to conduct a linguistic analysis of the sociolect(s) used by the slum dwellers in three areas of Lahore: Bahria Town, Model Town, and Wapda Town. The objectives were to find the sociolect(s) spoken by the slum community, analyze it based on linguistic features, and determine the extent the sociolect(s) of slum dwellers vary from the city dwellers. It has been years since the phenomenon of language was discovered and used by humans as the source of conveying perceptions. The qualitative research methodology and the two instruments: non-participant overt observation and semi-structured interviews have been used. The results elicited that the sociolects used by the slum community were mainly Punjabi, a mixture of both Urdu and Punjabi, and a hint of Saraiki was also found. Additionally, it is recommended to increase the sample size, incorporate participant observation, and conduct pilot testing to ensure clarity for the main study.